Body functionality: A review of the literature. (March 2021) - Alleva, Jessica M.; Tylka, Tracy L.
Highlights: Body functionality is valuable with respect to positive body image and well-being. Beyond functionality awareness, functionality appreciation is particularly important. A multifaceted and holistic conceptualisation of body functionality is also important. The experience of body functionality is nuanced across social identities. Abstract: Body functionality describes everything that the body is able to do, across diverse domains (e.g., bodily senses, creative endeavours). Nearly a decade ago, leading scholars identified research on body functionality as a priority for the body image field. The field has responded, as shown by the recent rise of body functionality research. We considered this an opportune time to (a) define body functionality (what it is and is not ); (b) present theoretical frameworks of body functionality; (c) articulate first-generation and current measures relating to body functionality; (d) offer functionality-focused body image interventions that can improve appreciation for one's body functionality (and body image more broadly); (e) summarise additional areas of research related to body functionality and positive body image; and (f) provide considerations and directions for future research and interventions incorporating body functionality. Research has underscored body functionality as a valuable construct with respect to positive body image and well-being, particularly when individuals appreciate what their bodies can do and conceptualise their body functionality holistically. Yet, the experience of body functionality is nuanced across social identities. Overall, the field has greatly advanced knowledge about body functionality, and we are excited to see the next generation of research that emerges.